Simultaneous, Bilateral Acute Subscapularis Ruptures and Their Arthroscopic Management - Andrew M. Schwartz; Jacob M. Wilson; Kyle Hammond (Case Reports in Orthopedics)
We present the first known case of bilateral, acute ruptures of the subscapularis tendons following a bicycle accident in a 43-year-old male. He underwent right shoulder arthroscopic, anatomic subscapularis tendon repair two weeks postinjury, with the left side staged for surgical treatment six weeks after the index procedure. Postoperatively, the patient remained in a sling for 6 weeks before advancing with therapy protocols. The interval between arthroscopic treatments allowed for independence with activities of daily living and focused, early therapy for each shoulder. This approach yielded a right-sided constant score of 89 and subjective shoulder value of 90%; the left side was 87 and 90%, respectively, at 33 months postoperatively. The patient’s only postoperative complaint was slightly diminished external rotation, a near-universal limitation after unilateral repair. This represents a successful outcome that balances functional independence, concentrated rehabilitation, and adherence to safe indications for primary repair. While bilateral traumatic shoulder injuries in a young person is a rare clinical entity, early and staged treatment can lead to good patient outcomes.